XFEM/Level-set for modelling of coated inclusion composites - Binh, Tran Anh (Vietnam Journal of Mechanics, 2017)
In this paper, Extended Finite Element method (XFEM) is used to model the embedded coated inclusion composite. The coated inclusion with finite thickness is associated with two level-set functions, which describe its inside and outside interfaces. A simple integration rule is employed for numerical quadrature in elements cut by two interfaces. Accuracy and efficiency of the proposed approach are demonstrated through 3D numerical examples and applied to homogenization of such materials.